Large palindromes on the primate X Chromosome are preserved by natural selection - Jackson, Emily K.; Bellott, Daniel W.; Cho, Ting-Jan; Skaletsky, Helen; Hughes, Jennifer F.; Pyntikova, Tatyana; Page, David C.

(untitled) (Genome Research, 2021)
Mammalian sex chromosomes carry large palindromes that harbor protein-coding gene families with testis-biased expression. However, there are few known examples of sex-chromosome palindromes conserved between species. We identified 26 palindromes on the human X Chromosome, constituting more than 2% of its sequence, and characterized orthologous palindromes in the chimpanzee and the rhesus macaque using a clone-based sequencing approach that incorporates full-length nanopore reads. Many of these palindromes are missing or misassembled in the current reference assemblies of these species’ genomes. We find that 12 human X palindromes have been conserved for at least 25 million years, with orthologs in both chimpanzee and rhesus macaque. Insertions and deletions between species are significantly depleted within the X palindromes’ protein-coding genes compared to their noncoding sequence, demonstrating that natural selection has preserved these gene families. The spacers that separate the left and right arms of palindromes are a site of localized structural instability, with seven of 12 conserved palindromes showing no spacer orthology between human and rhesus macaque. Analysis of the 1000 Genomes Project data set revealed that human X-palindrome spacers are enriched for deletions relative to arms and flanking sequence, including a common spacer deletion that affects 13% of human X Chromosomes. This work reveals an abundance of conserved palindromes on primate X Chromosomes and suggests that protein-coding gene families in palindromes (most of which remain poorly characterized) promote X-palindrome survival in the face of ongoing structural instability.